Product market deregulation and the US employment miracle - Monique Ebell; Christian Haefke (Institute for the Study of Labor (IZA), 2006)
We consider the dynamic relationship between product market entry regulation and equilibrium unemployment. The main theoretical contribution is combining a job matching model with monopolistic competition in the goods market and individual wage bargaining. Product market competition affects unemployment by two channels: the output expansion effect and a countervailing effect due to a hiring externality. Competition is then linked to barriers to entry. We calibrate the model to US data and perform a policy experiment to assess whether the decrease in trend unemployment during the 1980's and 1990's could be attributed to product market deregulation. Our quantitative analysis suggests that under individual bargaining, a decrease of less than two tenths of a percentage point of unemployment rates can be attributed to product market deregulation, a surprisingly small amount.
Keywords: E24; J63; L16; O00; 330; product market competition; barriers to entry; wage bargaining; Gesamtwirtschaftliche Produktion; Marktstruktur; Monopolistischer Wettbewerb; Deregulierung; Arbeitsmarkt; Beschäftigung; USA